Roommates awarded with Dual-Degree Programme Academic Excellence Prize - UMP, PNC (2019)
It is definitely the sweetest memory for two roommates to share the stage during the first session of the 14th UMP Convocation Ceremony held at the Sports Complex, Gambang Campus today.